A whole-cell Lactococcus garvieae autovaccine protects Nile tilapia against infection - Bwalya, Patricia; Hang’ombe, Bernard M.; Gamil, Amr A.; Munang'andu, Hetron M.; Evensen, Øystein; Mutoloki, Stephen (PloS one, 2020)
The autovaccine was produced in-house using a bacterial isolate from a diseased fish from the target farm. Three groups of 150 fish each were injected with either 1) an oil-adjuvanted, inactivated whole cell autovaccine, 2) adjuvant only or 3) PBS (negative control). Approximately 660 degree days post vaccination, the fish were challenged with 9x105 cfu bacteria/fish by intraperitoneal injection and monitored for a further 28 days. Protection against infections was measured by lack of/reduced bacterial loads both by bacterial re-isolation and immunohistochemistry as well as absence of clinical signs/pathology. Significantly less L. garvieae (p<0.03) was re-isolated from either the adjuvant only or control groups compared to the vaccinated group. Furthermore, a significantly high amount (p<0.001) of anti-L. garvieae specific antibodies were observed in the vaccinated group compared to the adjuvant only or control groups at time of challenge. This coincided with protection against infection measured by absence/reduced L. garvieae re-isolation from internal organs, reduced clinical signs and lack of pathology in this group. In the adjuvant only and control groups, bacteria were re-isolated from the kidney, liver, spleen, brain and eyes during the first 14 days. The findings suggest that oil-based vaccines can protect tilapia against L. garvieae infection through an antibody mediated response.